2006
DOI: 10.1007/s10750-006-0270-5
|View full text |Cite
|
Sign up to set email alerts
|

Selection and validation of reference sites in small river basins

Abstract: Type-specific reference conditions that describe sites with no or only very minor anthropogenic disturbances are a basic requirement of the European Water Framework Directive. The reference condition approach implies a previous determination of criteria acceptable for the definition of near-natural stretches. In this paper, a methodology based on selection and validation procedures is applied to a Portuguese watershed to guide the identification of reference sites. The methodology consisted of three phases: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
10

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 38 publications
2
34
1
10
Order By: Relevance
“…For example, in southeastern Arkansas, Justus (2010) considered all lakes with available water-quality data and used field reconnaissance and intensive sampling to identify a reference lake as the one with the least impairment in each of their 4 lake classes. In Portugal, Chaves et al (2006) identified candidate lakes from maps and used field visits and validation with biological data to identify reference sites in the 6700-km 2 Mondego River basin. However, as the scale of study increases and becomes continent-wide, this level of intensive effort is not practical, and less-intensive screening is required.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in southeastern Arkansas, Justus (2010) considered all lakes with available water-quality data and used field reconnaissance and intensive sampling to identify a reference lake as the one with the least impairment in each of their 4 lake classes. In Portugal, Chaves et al (2006) identified candidate lakes from maps and used field visits and validation with biological data to identify reference sites in the 6700-km 2 Mondego River basin. However, as the scale of study increases and becomes continent-wide, this level of intensive effort is not practical, and less-intensive screening is required.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, river-types with higher human density tend to present higher degradation conditions and therefore reference sites can be quite rare (Matono, 2012). The least disturbed river-types are usually located in high altitude regions (and small drainage basins), frequently in isolated areas with difficult human access, far from the main human pathways (Chaves et al, 2006;Schinegger et al, 2011). The WFD defined abiotic descriptors for classifying streams and rivers into types (Annex II, Section 1 of the WFD) according to two alternative systems: (i) "system A", the fixed typology, is defined by ecoregions (according to Illies, 1978), based on the catchment area, catchment geology and altitude; (ii) "system B" uses five obligatory factors (latitude, longitude, altitude, geology and drainage area of the basin), and an additional group of optional factors.…”
Section: Mots-clésmentioning
confidence: 99%
“…According to Chaves et al (2006), natural and seminatural areas cover 43% of the catchment area, but the natural hydrology of the basin has been heavily changed by the construction of several major dams and hundreds of small weirs. These factors were taken into consideration during site selection, which was initially based on maps, literature review and a preliminary field campaign performed during early spring 2002.…”
Section: Study Area and Selection Of Sampling Sitesmentioning
confidence: 99%
“…1) are near-natural systems since they exclude streams in the vicinity of urban, industrial or intensely cultivated areas, or influenced by dams, water withdrawals, high density of roads or other structures or known to have fish stocking and fishing activity. All sites exhibit no or only minor evidence of human disturbance and have the expected riparian vegetation and good apparent in-stream habitat quality (for details see Chaves et al, 2006). For the present study, a site was considered as near-natural only if it had high ecological water quality, i.e.…”
Section: Study Area and Selection Of Sampling Sitesmentioning
confidence: 99%
See 1 more Smart Citation